Identification of Risks of Delays in the Construction of Jalan Animal Hospital - Mochamad Gaharu Dida Devedo; Ardhan Ismail; Ridzky Zul Asdi; Chalsi Mala Sari; Kartika Tristanto; Muhammad Ibadurrahman Arrasyid Supriyanto (JURNAL MANAJEMEN RISIKO, 2025)
Timely completion of hospital construction projects is crucial to support public health services, but delays are a common problem that has an impact on increased costs and delayed social benefits. This study aims to identify the risk factors for causing delays and analyze the level of significance in the case study of the construction of the Jalan Kehewanan Hospital in Tenggarong. This study uses a qualitative approach with primary data collected through semi-structured interviews with the implementing contractor. Data analysis is carried out by mapping identified risks into risk matrices based on likelihood and impact. The results of the study identified four main risk factors, namely (1) Design Changes, (2) High Rainfall, (3) Restrictions on Working Hours by Residents, and (4) Equipment Damage. The risk assessment showed that Design Change (value 15) and High Rainfall (value 12) were the two factors with the most significant High risk level, while the other two factors were at Medium levels. These findings imply that project management should prioritize mitigation strategies on aspects of internal design management and anticipation of external weather factors to ensure the smooth running of the project